2017
DOI: 10.1002/dta.2301
|View full text |Cite
|
Sign up to set email alerts
|

Codeine influences the serum and urinary profile of endogenous androgens but does not interact with the excretion rate of administered testosterone

Abstract: Today's doping tests involve longitudinal monitoring of urinary steroids including the testosterone glucuronide and epitestosterone glucuronide ratio (T/E) in an Athlete Biological Passport (ABP). The aim of this study was to investigate the possible influence of short-term use of codeine on the urinary excretion of androgen metabolites included in the steroidal module of the passport prior to and after the co-administration with testosterone. The study was designed as an open study with the subjects being the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The reduction in testicular weight following codeine use explains the associated reduction of testosterone bioavailability and disrupted spermatogenesis observed in this study. The decline in the circulatory concentrations of testosterone seen in codeine treatment aligns with previous reports [15][16][17][18]. The decline in serum and testicular levels of androgen and cessation of spermatogenesis observed in codeine-treated animals could be partly due to codeine-induced loss of testicular tissues, and impairment of testicular metabolism and function.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The reduction in testicular weight following codeine use explains the associated reduction of testosterone bioavailability and disrupted spermatogenesis observed in this study. The decline in the circulatory concentrations of testosterone seen in codeine treatment aligns with previous reports [15][16][17][18]. The decline in serum and testicular levels of androgen and cessation of spermatogenesis observed in codeine-treated animals could be partly due to codeine-induced loss of testicular tissues, and impairment of testicular metabolism and function.…”
Section: Discussionsupporting
confidence: 90%
“…Chronic use of opioids is associated with androgen deficiency [15][16][17][18]. Findings of Rubinstein and Carpenter [15] demonstrated that the highest odds of androgen deficiency are associated with opioids that maintain the most stable serum drug concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in testicular weight following codeine use explains the associated reduction of testosterone bioavailability and disrupted spermatogenesis observed in this study. The decline in the circulatory concentrations of testosterone seen in codeine treatment aligns with previous reports [15][16][17][18]. The decline in serum and testicular levels of androgen and cessation of spermatogenesis observed in codeine-treated animals could be partly due to codeine-induced loss of testicular tissues, and impairment of testicular metabolism and function.…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, despite the enhanced sexual activity observed in rabbits administered with codeine, serum levels of testosterone were lower in them. Although no study has documented the effects of codeine or any opioid on sexual performance, findings from this study corroborate those that reported the anti‐androgenic activity of opioids (Eichenbaum et al , ; Daniell, ; Rubinstein & Carpenter, ; Lehtihet et al , ). Studies have reported a decline in serum levels of testosterone in tramadol‐treated rats via oxidative stress‐mediated testicular damage (Nna & Osim, ; Nna et al , ).…”
Section: Discussionmentioning
confidence: 99%